2017
DOI: 10.1038/srep46147
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the significance of morphological diversity for cerebellar granule cell excitability

Abstract: The relatively simple and compact morphology of cerebellar granule cells (CGCs) has led to the view that heterogeneity in CGC shape has negligible impact upon the integration of mossy fibre (MF) information. Following electrophysiological recording, 3D models were constructed from high-resolution imaging data to identify morphological features that could influence the coding of MF input patterns by adult CGCs. Quantification of MF and CGC morphology provided evidence that CGCs could be connected to the multipl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 68 publications
(103 reference statements)
3
31
0
1
Order By: Relevance
“…For example, in hippocampus CA1, AcD cells show higher excitability to synaptic input and generate APs with lower activation thresholds (Thome et al, 2014 ). A similar phenomenon was recently observed after electrophysiological recording and modeling of mouse cerebellar granule cells (Houston et al, 2017 ). Further, about 1/3 of all evaluated thick-tufted pyramidal cells in somatosensory cortex layer V give rise to axons from dendrites and are further characterized by a reduced dendritic complexity and thinner main apical dendrites (Hamada et al, 2016 ).…”
Section: Introductionsupporting
confidence: 83%
See 1 more Smart Citation
“…For example, in hippocampus CA1, AcD cells show higher excitability to synaptic input and generate APs with lower activation thresholds (Thome et al, 2014 ). A similar phenomenon was recently observed after electrophysiological recording and modeling of mouse cerebellar granule cells (Houston et al, 2017 ). Further, about 1/3 of all evaluated thick-tufted pyramidal cells in somatosensory cortex layer V give rise to axons from dendrites and are further characterized by a reduced dendritic complexity and thinner main apical dendrites (Hamada et al, 2016 ).…”
Section: Introductionsupporting
confidence: 83%
“…It seems logical that the further the AIS is located distally from the soma, the more the AP generation is uncoupled from somatic input. In fact, as shown by recent studies, this results in higher excitability to synaptic input and decreased activation thresholds for AP generation in hippocampal AcD cells (Thome et al, 2014 ) and cerebellar granule cells of this morphology (Houston et al, 2017 ). Generally speaking, the optimal AIS length and/or location (that of the most excitability, regardless of whether this is positive or negative for the cell) should be depending on the balance of depolarizing drive and its electrical isolation from the conductance load via the somatodendritic domain (Kuba et al, 2006 ; Baranauskas et al, 2013 ).…”
Section: Discussionmentioning
confidence: 73%
“…It was already known that GrC of vestibulo-cerebellum are specialized to slowdown firing modulation based on the expression of low-threshold calcium channels (Heath et al, 2014). Therefore, despite their morphological homogeneity, GrCs have differentiated conductance tuning and ionic channel expression, which could be further modified by fine variants in dendritic/axonal organization (Houston et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Conventionally, mature GCs are described to have 3–5 dendrites emerging from the soma. However, a recent study showed that nearly half of mature GCs had branched dendrites; a set of two dendrites that consists of one primary dendrite (emerging from the soma) and one secondary dendrite (emerging from the primary dendrite) 11 . The same study also showed that GCs with branched dendrites (branched GCs) receive more MF inputs than GCs with unbranched dendrites (unbranched GCs), suggesting that the branched GCs and unbranched GCs have a different degree of significance in neuronal computation in the GC layer.…”
Section: Resultsmentioning
confidence: 99%
“…The simplicity and compactness of this arbor combined with the ease of identification of the synapses are highly favorable for following the development of individual dendrites and its relationship with the formation of the claw (the site for synaptic contact on these neurons). Recent studies show that the size and pattern of the GC dendritic arbor are key for its function in the cerebellar circuitry 11 . Computational analysis shows that GCs allow high-dimensional representation of incoming sensorimotor information, conveyed by MFs, most efficiently when each GC has four dendrites 12 .…”
Section: Introductionmentioning
confidence: 99%